PENGARUH HARGA DAN SUASANA KAFE DI KAWASAN SENGGIGI TERHADAP KEPUTUSAN PEMBELIAN PADA MAHASISWA - I Putu Septian Adi Prayuda; Fathurrahman, Fathurrahman; Slamet Mardiyanto Rahayu; Lale Ajeng Khalifatun Wardani (Yayasan Nusantara Hasana Berdikari, 2025)
Senggigi is a popular tourist destination in West Nusa Tenggara. Price and cafe atmosphere are factors that determine purchasing decisions for a product. Based on research, it can be seen that the price and atmosphere of cafes in the Senggigi area greatly influence students' purchasing decisions.